Rendering swearing across cultures: arabic professional subtitles and fansubs of pulp fiction - Yousef Sahari (Cogent Arts & Humanities)
Due to the prevalence of swearing in popular Hollywood films, a cross-cultural challenge arises when translating these films into socio-cultural contexts where swearing is more severely proscribed. The present study aims to investigate how swear words are translated into Arabic and whether significant differences exist between professional subtitles and those created by fans in terms of translation strategies. For this study, the film ‘Pulp Fiction’ (1994), written and directed by Quentin Tarantino, serves as a case study. A quantitative analysis was conducted to determine the frequency of swearing and the translation strategies used in the official DVD subtitles versus the internet fansubs. The goal was to ascertain whether significant differences exist between these two subtitled versions. In addition to the quantitative findings, a qualitative analysis is presented. The results indicate that fansubs tend to retain more swear words than official subtitles and that the choice of translation strategy is influenced by the type of swearing employed.